Lentiviral gene transfer to reduce atherosclerosis progression by long-term CC-chemokine inhibition. - Bursill, C; McNeill, E; Wang, L; Hibbitt, O; Wade-Martins, R; Paterson, D; Greaves, D; Channon, K (2009)
CC-chemokines are important mediators in the pathogenesis of atherosclerosis. Atherosclerosis progression is reduced by high-level, short-term inhibition of CC-chemokine activity, for example by adenoviral gene transfer. However, atherosclerosis is a chronic condition where short-term effects, while demonstrating proof-of-principle, are unlikely to provide maximum therapeutic benefit. Accordingly, we generated a recombinant lentivirus, lenti35K, encoding the broad-spectrum CC chemokine inhibitor, 35K, derived from the vaccinia virus. To investigate the effects of prolonged broad-spectrum chemokine inhibition on atherosclerosis, lenti35K, or lentiGFP or PBS were delivered to 6-week-old ApoE knockout (ApoE-KO) mice by hydrodynamic injection. Sustained lentiviral transduction and transgene expression were demonstrated by 35K mRNA and viral DNA in liver tissue, and recombinant 35K protein circulating in the plasma, 3 months after gene transfer. Plasma from lenti35K animals had reduced chemokine activity compared with plasma from lentiGFP or PBS-treated animals. Histologic analysis of aortic sinus sections revealed that atherosclerotic plaque area in lenti35K mice was significantly reduced compared with both lentiGFP and PBS controls. Furthermore, plaque macrophage content was substantially reduced in lenti35K mice. Lentiviral 35K gene transfer is a promising experimental strategy to reduce atherosclerosis progression, and demonstrates the potential of long-term CC-chemokine inhibition as a potential therapeutic target in atherosclerosis.